Referral Finder: Saving Time and Improving The Quality of In-hospital Referrals. Issue 1 (7th April 2016) - Cathcart, Jennifer; Cowan, Neil; Tully, Vicki
Abstract : Making referrals to other hospital specialties is one of the key duties of the foundation doctor, which can be difficult and time consuming. In Ninewells hospital, Scotland, in our experience the effectiveness of referrals is limited by contact details not being readily accessible and foundation doctors not knowing what information is relevant to each specialty. We surveyed foundation doctors on their experience of the existing referral process to identify where we needed to focus to improve the process. The doctors reported significant delays in obtaining contact details from the operator, and found they did not know the specific information needed in each referral. To increase the information available to foundation doctors, we set up a page on the staff intranet called 'Referral Finder'. This page includes contact details, guidelines for referral, and links to relevant protocols for each specialty. By making this information readily accessible our objective was to increase the speed and quality of referrals. When surveyed two months after the web page was established, foundation doctors reported a reduction in calls to operator from baseline and reported achieving more effective referrals. When asked to comment, many doctors asked if the page could include details for other hospitals in our health board and provide more specialty specific information. This feedback prompted us to extend the scope of the page to include the district general hospital in our region, and update many of the existing details. Doctors were then surveyed after the updates, 100% agreed that the website saved time and there was a 49.3% reduction in doctors who reported not knowing the specific information needed for a referral. Having adequate information improved referrals and resulted in time saved. This would allow more time for patient care. The quality improvement project was praised among doctors as a useful, innovative and replicable project.